Neuroestetyka w badaniach sztuki pradziejowej. Ocena potencjału - Markiewicz, Małgorzata (Folia Praehistorica Posnaniensia, 2025)
The article aims to assess the potential of neuroaesthetics in the study of ornamentation, as well as the form and style of archaeological artefacts. Neuroaesthetics, as a research approach, suggests incorporating the mechanisms of human brain function into the analysis of art creation and perception. Traditional studies of prehistoric art primarily focus on cultural context, often overlooking the biological aspect. By drawing on insights from cognitive science and neuroscience, it is possible to explore the physiological foundations of art. Analysis of contemporary research on the mind suggests that prehistoric artists, by adhering to the principles of perception and physiology, unconsciously stimulated specific areas of the viewer’s brain, leading to the emergence of aesthetic experiences.